Field Performance and Genetic Parameters of Newly Introduced Tree Willow (Salix Species) Clones - Sharma, J. P.; Singh, N. B.; Thakur, I. K.; Chaudhary, Punit (Indian Forester, 2015)
The species and hybrids of willows were procured during 2002-04 from twenty countries and subjected to nursery screening. To test the field performance the selected 15 promising clones were planted in farmers fields in March, 2007. The five years growth performance depicted that clone J-194 had highest plant height (16.66 m), diameter at breast 3 height (19.97 cm) and volume index (0.679m3) along with most straight bole (4.60). The clones Kashmiri willow (16.08 m) and PN-722 (16.00 m) were at par with J-194 for height growth followed by the clones NZ1002 (15.18 m), J-799(14.63 m), J-795 (13.38 m) and PN-733 (13.34 m). The clones PN-722 (18.82 cm) and J-799 (17.80 cm) showed diameter growth (DBH) at par with clone J-194. Straightness of J-799 (4.50), J-795(4.38), SI-63-007(4.21), SI-64-017(4.09), PN 722 (4.04) and V-99(3.75) clones was at par with J-194. Heritability estimates (broad sense) of the traits ranged from 64.80 per cent in volume index to 94.67 per cent in bole straightness. On the basis of initial screening in field conditions clones namely J-194, J-799, J-795, PN 722 and NZ 1002 were found suitable for large scale plantation in this area.